Effect of miRNA-7 on the tumorigenesis of EGFR-overexpressing CD133+ and CD133- non-small cell lung cancer cells - Kruger, Natasia J (My University, 2016)
Currently, non-small cell lung cancer (NSCLC) accounts for 80% of lung cancer diagnoses. Even with chemotherapy treatment options, the five year survival rate of patients with NSCLC is only 15%. Cancer stem cells (CSC) are a subpopulation of tumour cells that have the capacity to self-renew and are thought to be responsible for the chemoresistance seen in cancers such as NSCLC. Also associated with chemoresistance is the epidermal growth factor receptor (EGFR), that is overexpressed in some 39% of NSCLC adenocarcinomas. In this study, the role of EGFR in an in vitro model of NSCLC cancer stem cell chemoresistance is evaluated. A549 NSCLC cells were separated into CSCs and non-CSCs, based on differential expression of the cell surface marker CD133; CSCs being designated as CD133+ and non-CSCs as CD133−. The CD133 surface expression was verified in the putative CSC population by immunofluorescence microscopy. The stem cell properties of the CD133 positive cell population were affirmed by their ability to form 3D spheroids in cell culture, relative to the adherent monolayers of the negative cell population. Moreover, some 99% of the CD133+ cells, as shown by FACS analysis, possessed the ability to efflux Hoechst 33342 via the ATP-binding cassette (ABCG2) transporters, this being a distinctive feature of stem cells. Using cell scratch assays, the migration rate of the CSCs was determined to be 1.92 fold lower as compared to non-CSCs. Furthermore, CSCs were significantly more chemoresistant than non-CSCs to a 48 hour 20nM treatment of Paclitaxel (IC50), a conventional chemotherapeutic agent, with viabilities of 71.3% and 47.0%, respectively (P<0.05). With regard to EGFR expression, EGFR mRNA levels were approximately 16 fold higher in CSCs, compared with non-CSCs, when normalised against 4 reference genes (P< 0.01). Analysis of protein expression by confocal microscopy similarly showed elevated EGFR expression, of approximately 1.7-fold relative to non-CSCs (P<0.0001), with a 4-fold increased mean expression of CD133 in the CSCs (P<0.0001). To further investigate the role of EGFR in CSCs and non-CSCs, knockdown studies were performed, targeting miRNA-7, a known down-regulator of EGFR expression. Stable lentiviral transduction of U1-pri-miR-7-1 in pHIV-7-GFP was validated in non-CSCs with flow cytometry, which indicated a 97.9% transduction efficiency. Western blotting revealed no visible knockdown in non-CSCs; and this may relate to a point mutation found near the 3’ end of the pri-miR-7 sequence, as demonstrated by sequencing analysis. Confocal microscopy of the miR-7 transduced non-CSCs showed a differential localisation of EGFR in the nucleus, not present in the miR-107 control. It is plausible here that the miR-7 mutant causes nuclear localisation of EGFR in the absence of a knockdown effect. This finding may be of relevance, since nuclear EGFR is associated with a poorer prognosis in many tumour types and has been shown to be responsible for resistance to tyrosine kinase inhibitor therapies. In summary, the raised expression of EGFR together with CD133, compared to the non-CSCs may be consistent with the maintenance of this NSCLC stem cell population, mediating chemoresistance through increased ABCG2 cell surface expression. Moreover, the identification of regulatory mechanisms in such chemoresistant lung CSCs may ultimately help to develop novel, effective therapies to alleviate tumour burden. Keywords: Non-small cell lung cancer, CD133, EGFR, Cancer Stem Cells, A549, chemoresistance, Paclitaxel, microRNA-7
A thesis submitted by the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science Johannesburg, 2016